Reduced DNA methylation of sphingosine‐1 phosphate receptor 5 in alveolar macrophages in COPD: A potential link to failed efferocytosis. Issue 2 (20th November 2016) - Barnawi, Jameel; Jersmann, Hubertus; Haberberger, Rainer; Hodge, Sandra; Meech, Robyn
ABSTRACT: Background and objective: We previously showed that alveolar macrophages from COPD patients are defective in their ability to phagocytose apoptotic cells ('efferocytosis') and that this defect is potentially linked to the sphingosine‐1 phosphate (S1P) system, in particular the sphingosine‐1 phosphate receptor 5 (S1PR5). In alveolar macrophages from COPD patients, S1PR5 mRNA expression levels increased and were correlated with both lung function and efferocytosis. However, it us unknown whether these changes are under epigenetic control via DNA methylation or whether DNA methylation directly modulates macrophage function. Methods: Bisulfite sequencing was used to assess DNA methylation levels at CpG islands associated with genes encoding selected S1P system components, including sphingosine kinase 1 (SPHK1), S1PR1 and S1PR5, in alveolar macrophages from 20 COPD patients, 7 healthy smokers and 10 healthy non/ex‐smokers) by methyl quantitative real‐time PCR (methyl qPCR). The effect of the DNA methyltransferase inhibitor, 5‐azacytidine on the efferocytosis capacity of THP‐1 macrophages was assessed using flow cytometry. Results: Among the S1P system genes examined, S1PR5 was the single target that showed significant changes in DNA methylation between patient groups. Alveolar macrophages isolated from COPD patients showed lower methylation levels in the same region compared to macrophages from non/ex‐smokers. in vitro studies using THP‐1 macrophages showed that DNA demethylation with 5‐azacytidine increased the efferocytosis capacity and dose‐dependently rescued the cells from the cigarette smoke‐induced defect in efferocytosis. Conclusion: Macrophage function can be modulated epigenetically. Reduced methylation may underlie the increased expression of the S1PR5 gene in alveolar macrophages and associated defective efferocytosis in COPD. Abstract : We describe for the first time the potential linkage of dysregulated sphingosine‐1 phosphate receptor 5 (S1PR5) methylation and expression, to the reduced alveolar macrophage efferocytic function in COPD and its potential to contribute to tissue damage and chronic airways inflammation.